At the Heart of Freedom : Feminism, Sex, and Equality. - Cornell, Drucilla (Princeton University Press, 2001)
How can women create a meaningful and joyous life for themselves? Is it enough to be equal with men? In this provocative and wide-ranging book, Drucilla Cornell argues that women should transcend the quest for equality and focus on what she shows is a far more radical project: achieving freedom. Cornell takes us on a highly original exploration of what it would mean for women politically, legally, and culturally, if we took this ideal of freedom seriously--if, in her words, we recognized that "hearts starve as well as bodies." She takes forceful and sometimes surprising stands on such subjects.